Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Bank Rakyat Indonesia, Tbk Kantor Cabang Rantepao, Kabupaten Toraja Utara - Alicia Tiara Pamangin; Chrismesi Pagiu; Marchelin Marchelin (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine the effect of workload and work environment on employee job satisfaction at PT. Bank Rakyat Indonesia, Tbk Rantepao Branch Office, North Toraja Regency. The object in this study is Employees at PT. Bank Rakyat Indonesia, Tbk Rantepao Branch Office, North Toraja Regency. This study used a quantitative approach with multiple linear regression analysis, to test and prove the hypothesis of this study using SPSS application version 26. The population in this study is permanent employees at PT. Bank Rakyat Indonesia, Tbk Rantepao Branch Office, North Toraja Regency as many as 103 respondents. This research shows that Workload and Work Environment do not affect together. By testing the coefficient of determination, a value of 0.269 or 26.9% was obtained. The Job Satisfaction variable can be explained by the Workload and Work Environment variables while the remaining 73.1% is explained by other variables.